نظريّات أسلوب تعبير الصور في تعليم مهارة الكتابة أحمد جعفر صادق - Achmad Ja'far Sodik (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
Abstract In the language teaching has four language skills are listening skills, speech skills, reading skills, and writing skills. Writing is a fourth skill in terms of ranking in education.Skill writing is the most important material between subjects. This Article discuss what are the theories of the image description technique in the learning of writing skills and how to implement in the learning of writing skills. The description technique in the teaching of writing skill is the technique used to find the idea in the expression of images and to make organizational writing in the teaching of writing skill. There are also types of expression of images, and steps in teaching the skill of writing, the main result is that the implementation of the images description technique in the teaching of writing skill contains three stages is the stage before writing, writing stage, and post-writing. Keyword:  Theories, Technique, Image Description, Writing Skill